2023
DOI: 10.1186/s40337-023-00917-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of short-chain fatty acids (SCFAs) in regulating stress responses, eating behavior, and nutritional state in anorexia nervosa: protocol for a randomized controlled trial

Robin Quagebeur,
Boushra Dalile,
Jeroen Raes
et al.

Abstract: Objective This protocol proposes investigating the effects of short-chain fatty acids (SCFAs)—namely acetate, propionate, and butyrate—as mediators of microbiota-gut-brain interactions on the acute stress response, eating behavior, and nutritional state in malnourished patients with anorexia nervosa (AN). SCFAs are produced by bacterial fermentation of dietary fiber in the gut and have recently been proposed as crucial mediators of the gut microbiota's effects on the host. Emerging evidence sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Although the actual mediator that connects BL in the gut and brain of ICV Aβ-injected mice could not be elucidated in this study, BL-derived short-chain fatty acids (SCFAs), such as butyrate, propionic acid, and acetate, may be possible candidates for transmitting the beneficial effects of BL in the mouse gut to the brain. SCFAs produced by the gut microbiota are known to play critical roles in many physiological processes such as metabolism, immunological responses, and intestinal integrity ( Quagebeur et al, 2023 ). In addition, studies have shown that SCFAs produced by the gut microbiota move into the bloodstream and finally reach the brain by penetrating the blood-brain barrier ( Kekuda et al, 2013 ; Oldendorf, 1973 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the actual mediator that connects BL in the gut and brain of ICV Aβ-injected mice could not be elucidated in this study, BL-derived short-chain fatty acids (SCFAs), such as butyrate, propionic acid, and acetate, may be possible candidates for transmitting the beneficial effects of BL in the mouse gut to the brain. SCFAs produced by the gut microbiota are known to play critical roles in many physiological processes such as metabolism, immunological responses, and intestinal integrity ( Quagebeur et al, 2023 ). In addition, studies have shown that SCFAs produced by the gut microbiota move into the bloodstream and finally reach the brain by penetrating the blood-brain barrier ( Kekuda et al, 2013 ; Oldendorf, 1973 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that SCFAs produced by the gut microbiota move into the bloodstream and finally reach the brain by penetrating the blood-brain barrier ( Kekuda et al, 2013 ; Oldendorf, 1973 ). SCFAs are endogenous ligands that regulate gene expression by binding to G protein-coupled receptors ( Quagebeur et al, 2023 ) and attenuating the activity of histone deacetylases ( Fischer et al, 2007 ; Schroeder et al, 2007 ). Therefore, although the effects of BL on the changes in SCFAs in our animal study were not determined, BL-mediated SCFAs may affect gene regulation related to cognitive impairment in the brain tissue of an AD-like mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The SCFAs butyrate, propionate, and acetate are important products of bacterial fermentation in the human intestine and are known to have the ability to regulate anxiety-like behavior ( 35 ). Emerging research has demonstrated that SCFAs may regulate the effects of gut bacteria on stress responses of the HPA axis and attenuate the cortisol response to acute psychosocial stress ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota has various effects on host physiology, including host metabolism, the development of the immune system, and even behaviors [51]. The complex interplay between the gut, stress, and eating/drinking behavior may facilitate new therapeutic targets for stress-related psychiatric disorders [51].…”
Section: Connection Between Gut Microbiota and Alcohol Dependencymentioning
confidence: 99%
“…The gut microbiota has various effects on host physiology, including host metabolism, the development of the immune system, and even behaviors [51]. The complex interplay between the gut, stress, and eating/drinking behavior may facilitate new therapeutic targets for stress-related psychiatric disorders [51]. Remarkably, short-chain fatty acids (SCFAs), namely acetate, propionate, and butyrate, might be mediators of microbiota-gutbrain interactions on the stress response and/or eating/drinking behavior.…”
Section: Connection Between Gut Microbiota and Alcohol Dependencymentioning
confidence: 99%